Type I IFN and TNFα cross-regulation in immune-mediated inflammatory disease: basic concepts and clinical relevance - Cantaert, Tineke (BioMed Central, 2010)
A cross-regulation between type I IFN and TNFα has been proposed recently, where both cytokines are hypothesized to counteract each other. According to this model, different autoimmune diseases can be viewed as disequilibrium between both cytokines. As this model may have important clinical implications, the present review summarizes and discusses the currently available clinical evidence arguing for or against the proposed cross-regulation between TNFα and type I IFN. In addition, we review how this cross-regulation works at the cellular and molecular levels. Finally, we discuss the clinical relevance of this proposed cross-regulation for biological therapies such as type I IFN or anti-TNFα treatment.